Potential Consequences of Abandonment in Preschool-Age: Neuropsychological Findings in Institutionalized Children - Juan F. Cardona; Facundo Manes; Josefina Escobar; Jéssica López; Agustín Ibáñez (Behavioural Neurology)
Objective: Several longitudinal studies had shown that early deprivation and institutionalization during the first six months of life affects the emotional, cognitive, social and neurophysiologic development. Nevertheless, our understanding of possible similar effects of delayed institutionalization, in preschool-age remains unclear to this day. The goal of this study is to evaluate the cognitive performance of institutionalized children with history of preschool-age physical abandonment.